2007
DOI: 10.1007/s11606-007-0333-y
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Depression in Medical Settings with the Patient Health Questionnaire (PHQ): A Diagnostic Meta-Analysis

Abstract: The PHQ9 is acceptable, and as good as longer clinician-administered instruments in a range of settings, countries, and populations. More research is needed to validate the PHQ2 to see if its diagnostic properties approach those of the PHQ9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
811
1
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,085 publications
(874 citation statements)
references
References 56 publications
19
811
1
18
Order By: Relevance
“…Although our ability to diagnose major depression was limited by our use of a questionnaire to assess depressive symptoms and not a diagnostic interview, the questionnaire we used has been validated in our study population and has acceptable sensitivity and specificity compared to structured diagnostic interview. 17,18 Also, self-report of baseline factors such as physical inactivity, smoking, and BMI may not accurately reflect subsequent health behaviors over the follow-up period. Though we only measured depression at baseline and depression status may have changed over the course of follow-up, a related study in patients with diabetes found that over 70 % of patients with a PHQ-9 score ≥ 10 reported that they had been depressed for more than 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our ability to diagnose major depression was limited by our use of a questionnaire to assess depressive symptoms and not a diagnostic interview, the questionnaire we used has been validated in our study population and has acceptable sensitivity and specificity compared to structured diagnostic interview. 17,18 Also, self-report of baseline factors such as physical inactivity, smoking, and BMI may not accurately reflect subsequent health behaviors over the follow-up period. Though we only measured depression at baseline and depression status may have changed over the course of follow-up, a related study in patients with diabetes found that over 70 % of patients with a PHQ-9 score ≥ 10 reported that they had been depressed for more than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 14 studies found that the PHQ-9 threshold for a probable case of major depression had a pooled sensitivity of 80 % and specificity of 92 % compared to structured psychiatric interviews. 18 We also examined probable minor depression (defined as the presence of two to four depressive symptoms, one of which is either depressed mood or anhedonia, for more than half the days for at least 2 weeks) as a comparison condition, since prior studies have found minor depression was associated with increased healthcare costs, rehospitalization, and mortality in patients with chronic medical illnesses. [19][20][21] The sensitivity and specificity of the PHQ-9 for identifying a probable case of minor depression compared to structured psychiatric interview has been shown to be 77 % and 86 %, respectively.…”
Section: Primary Independent Variablementioning
confidence: 99%
“…Respondents rate how much each symptom has been bothering them during the last two weeks using a 4-point scale from 0 ‘not at all’ to 3 ‘almost every day’. The instrument has shown good psychometric properties and adequate validity as a measure of symptoms of depression (Gilbody, Richards, Brealey, & Hewitt, 2007; Kroenke et al, 2001). …”
Section: Methodsmentioning
confidence: 99%
“…The PHQ-9 is a nine-item questionnaire that asks respondents to indicate the frequency with which they experience each of the nine symptoms considered in the diagnostic criteria for major depression [28]. The PHQ-9 has been shown to be a valid and reliable measure of depressive symptoms in patients with a variety of medical conditions [11,14,19].…”
Section: Methodsmentioning
confidence: 99%